Heck-type hydroarylations and 1,3-dipolar cycloaddition reactions of new tricyclic hydrazones - Gul, Melek; Ocal, Nuket (CANADIAN SCIENCE PUBLISHING, 2010)
The C-C coupling of the new tricyclic hydrazones 3-7 with aryl and heteroaryl halides gave under reductive Heck conditions the tricyclic 1-(arylideneamino)pyrolidine-2,5-diones 8-11a, 9-11b, 10c, and 12. The [3+2] cycloadditions of 3-7 with p-chlorophenyl nitrile oxide (13) yielded the bridged isoxazoline derivatives 14-18 with potential biological activity.
Keywords: tricyclic hydrazone; reductive Heck reactions; C-C coupling; nitrile oxides; isoxazolines; IRON CHELATORS; CHEMISTRY; EPIBATIDINE